Developing an Online Course Book for English Freshmen in Lamongan Universities - Fariq Shiddiq Tasaufy; Syifa' Khuriyatuz Zahro (Lingua, 2020)
Until these days, the possibility of face-to-face teaching learning process in any universities is quite low. Therefore, the need of online learning materials for online or/and blended learning is inevitable. The present research aimed to develop an onlinebook for Reading 1 course at 3 universities in Lamongan. Unlike other online ELT books which is western-oriented, this online course book was developed based on Lamongan-Javanese’ local wisdom. A total of 135 freshmen and 3 lecturers were involved as the subjects. The results of need analysis showed that 1) the freshmen have positive attitude towards English reading even though they confronted by some problems, 2) the lecturers seemed to have different interpretations on their freshmen’ reading preferences, and 3) the students’ reading comprehension level needed to be improved. A number of implications regarding these findings were discussed as well in this research.